Long-term outcome after revision of hip arthroplasty with the BioBall® adapter system in multimorbid patients - Kock, Hans-Jürgen; Cho, Christopher; Buhl, Klaus; Hillmeier, Joachim S.; Huber, Franz-Xaver (Journal of orthopaedic translation, 2020)
Introduction - Long-term study evidence about the BioBall® adapter system is limited, especially in highly morbid elderly patients. Thus, we analysed the long-term outcome of revision hip arthroplasty using this system in highly morbid elderly patients. - Materials and methods - We included 19 patients undergoing revision hip arthroplasty after primary or secondary total hip arthroplasty dislocations between July 2002 and August 2004 and followed up their long-term outcome until 2015. - Results - The patients achieved a median of 17 points in the Merle d'Aubigné hip score in 2004 and a median of 18 points in 2011, and the 4 surviving patients in 2015 achieved 18 points. For the four 12-year survivors, the Merle d'Aubigné score was virtually stable over the complete observation period. The Harris Hip Score showed comparable results. The patients had a median Barthel index of 90 in 2004 and 100 in 2011, and the 4 survivors in 2015 had Barthel indices of 65, 95, 100, and 100, respectively, in 2015. - Conclusions - In multimorbid patients, using the BioBall® adapter system for total hip arthroplasty, revision due to dislocation results in good long-term outcome without impairment of quality of life. - Translational potential - Our study provides long-term evidence in a vulnerable patient population. It shows how the therapeutic concept of revision hip replacement with an adapter device translates into long-term outcome and quality of life in these patients. Thus, it adds important information for evaluation of therapeutic options in this field.
Available online 20 September 2019
Im Titel ist das R im Kreis und hochgestellt
Gesehen am 19.03.2021